OPERATIVE MANAGEMENT OF CLOSED ANKLE FRACTURE WITH AO TECHINQUE - Khan, Muhammad Ayaz; Shafiq, Muhammad; Sahibzada, Ahmad Sohail (Journal of Postgraduate Medical Institute, 2011)
Objective: The purpose of the study was to assess the result of closed ankle fracture with open reduction and internal fixation (ORIF) with AO Technique. Materoal and Methods: This study was done on thirty patients at Ayub Teaching Hospital Complex, Abbotabad from Jan 2004 to Dec 2004. All the patients had closed bimalleolar fracture. The medial malleolus was fixed with two self tapping malleolar screws with washers and lateral malleolus was fixed with one third tubular plates. The overall results were graded as excellent, good, fair and poor. Results: In 26 patients (86.8%) fractures healed uneventfully and follow up were completed. Two patients (6.6%) developed wound infection, which were superficial and two patients (6.6%) developed skin necrosis. More complications were observed in patients who had high-energy trauma. Radiological and functional assessment was done at each follow up visit.. The results were excellent to good in 93.4%. Conclusion: Displaced closed bi- malleolar fractures should be addressed with open reduction and internal fixation using AO Technique to get functional and anatomical acceptable results.